What sort of Brexit do the British people want? A longitudinal study examining the 'trade-offs' people would be willing to make in reaching a Brexit deal. (December 2020) - Lu, Hui; Rohr, Charlene; Howarth, David; Pollitt, Alexandra; Grant, Jonathan
Abstract: In a referendum in March 2016, the British public voted by a margin of 52 per cent to 48 per cent to leave the European Union. Unfortunately, the referendum question provides little information on the sort of relationship Britons desire with the EU. The purpose of this study is to use stated choice experiments (CEs) to understand and quantify what aspects of the relationship between Britain and the EU are important to the public and what trade-offs they would be willing to make. The CEs are undertaken with a random probability sample of the public at two points in time, 2017 and 2018, to allow us to explore how preferences might have changed over time. We developed a series of discrete choice models ranging from Scaled Multinomial Logit models (SMNLs) to Latent Class models (LCMs) to understand and quantify public preferences and to explore how they vary across the population. The results are used to assess how positively or negatively the public value different plausible Brexit negotiation positions.